On Classification of Finite-Dimensional Superbialgebras and Hopf Superalgebras - Aissaoui, S.; Makhlouf, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
The purpose of this paper is to investigate finite-dimensional superbialgebras and Hopf superalgebras. We study connected superbialgebras and provide a classification of non-trivial superbialgebras and Hopf superalgebras in dimension n with n≤4.